AN EFFECTIVE AND PHYSIOLOGICAL LIFESTYLE CHANGE FOR MANAGEMENT OF GASTROESOPHAGEAL REFLUX DISEASE - Randhawa, Mohammad A; Yar, Taley; Gillessen, Anton (Journal of Ayub Medical College Abbottabad, 2013)
<p class="MsoNormal" style="margin-top: 0in; margin-right: .5in; margin-bottom: .0001pt; margin-left: .5in; text-align: justify; text-justify: kashida; text-kashida: 0%; mso-outline-level: 1; direction: ltr; unicode-bidi: embed;">Abstract: Proton pump inhibitors (PPIs) are commonly used in the treatment of gastro-oesophageal reflux disease (GERD). Some disadvantages of these acid- suppressing drugs circulate and patients ask for alternatives. Transient lower oesophageal sphincter relaxations (TLESRs) are important cause of reflux. Gastric distension in upper stomach are strongest stimulus for generation of TLESRs and is aggravated by intake of food in between meals. In the light of pathophysiological mechanisms it is suggested that increasing interval between meals and only soft drinks in between will reduce reflux episodes. The hypothesis was tested in 4 patients with endoscopically proven reflux oesophagitis and/or typical reflux symptoms. Three patients followed our advice to eat twice a day, with soft drinks in between. One patient had a light breakfast but increased the interval between lunch and dinner to 8 hours.All cases were relieved from repeated reflux episodes, in 1-2 weeks, without any medication. <span style="font-size: 10.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; letter-spacing: -.2pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">Keywords:<span style="font-size: 10.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’Times New Roman’; letter-spacing: -.2pt; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> GERD, pathophysiology, increased interval between meals, lifestyle changeAn effective and physiological lifestyle change for management of GASTROesophageal Reflux Disease